Ritual Pengikut Tarekat Shâdhilîyah di Tambak Beras, Jombang-Jawa Timur - Abdullah Safik (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2011)
This article tries to phenomenologically examine the existence of the Shâdhilîyah tarekat supervised by KH. Djamaluddin in Tambak Beras, Jombang. The Shâdhîlîyah tarekat, which had been initiated by Abû Hasan al-Shâdhilî, is exceptional and consistent in holding and practicing its tawhid principle as well as dhikr rituals. In Indonesia, this tarekat has rapidly evolved. One of its murshid is KH. Abdul Jalil Mustaqim in Tulungagung, the murshid to KH. Djamaluddin. The tarekat has two main doctrines, are: firstly, the ‘ubûdîyah realm where its followers are obliged to physically and mentally obey Allah SWT and His messenger, i.e. the Prophet Muhammad, in all their sayings and deeds. Secondly, mu‘âmalah aspect where each follower is taught to interact with other people and creatures only for the sake of Allah. It means that the tarekat is a medium of self approaching to Allah. One of the special rites (khusûsîyah) conducted by this tarekat is an every-Tuesday agenda where dhikr, tawassul, tahlîl, and tahmîd activities are held. Technically, a sâlik when s/he recites dhikr should be followed by breathing in which is concentrated in the navel and going on top through the thoracic cavity and coming out through the mouth then retracting it back to tongue.